Hubungan Disfungsi Endotel dengan Preeklamsia Gejala Pemberat - Angelie Cahya Putri; Nurul Islamy; Anisa Nuraisa Jausal; Suharmanto Suharmanto (Medula, 2026)
Preeclampsia with severe features is a major pregnancy complication contributing substantially to maternal and perinatal morbidity and mortality worldwide. This condition primarily arises from impaired placentation that leads to placental hypoperfusion and the release of anti-angiogenic factors such as sFlt-1 and soluble endoglin, which suppress pro-angiogenic activity of VEGF and PlGF, ultimately triggering systemic endothelial dysfunction. This review aims to analyze the relationship between endothelial dysfunction and the pathophysiological mechanisms of severe preeclampsia through current scientific literature. A narrative literature review was conducted, examining clinical and molecular studies related to angiogenesis, oxidative stress, inflammation, and biomarkers influencing disease progression. The findings indicate that angiogenic imbalance, increased oxidative stress, inflammatory activation, and hemodynamic alterations are key drivers of endothelial injury, resulting in hypertension, proteinuria, edema, and multi-organ involvement. Additionally, the sFlt-1/PlGF ratio is identified as a strong predictor of disease severity and progression toward severe preeclampsia. The discussion highlights that deeper understanding of endothelial mechanisms provides promising pathways for developing early screening tools and targeted therapeutic strategies. Thus, endothelial dysfunction represents a central component in the pathogenesis of severe preeclampsia and remains critical for improving detection and clinical management.